Polydopamine-vanillin surface-modified thin-film composite membrane to mitigate bacterial growth. Issue 5 (October 2022) - Park, Chansoo; Lei, Ji; Shin, Hyunseo; Kim, Jong-Oh
Abstract: Pretreatment with antibiotics is commonly used to mitigate biofouling. However, bacteria are resistant to antibiotics because biofouling protects them from chemical shearing and disinfection. In this study, membrane surfaces were modified with vanillin, a substance that can interfere with signaling between bacteria. Due to vanillin's desorption properties, polydopamine (PDA), a mussel-inspired material, was also used. We examined membrane surface properties and consequent changes in the antibacterial performance of vanillin. Water permeability was assessed with a reverse osmosis (RO) membrane simulator module, and a contact angle (CA) was used to analyze the hydrophilicity of the membrane samples. Furthermore, membrane surface morphology was evaluated by atomic force microscopy (AFM), and coated membranes were characterized by X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). Antibacterial and anti-adhesion effects were verified using petrifilm to count bacteria on the surface of modified membranes. We found that the water permeability of coated membranes was only slightly lower (2.44 L/m 2 /hr/bar to 2.12 L/m 2 /hr/bar) and hydrophilicity slightly lower than or greater than those of a pristine membrane (up to 30 % decrease in CA). Moreover, the number of bacteria colonies decreased. Results confirmed that a membrane samples with polydopamine co-deposited with vanillin for 2 h outperformed other coated membranes. Graphical Abstract: ga1 Highlights: Coating of membrane may possess short-term effects and toxicity in the environment. Vanillin is a natural compound that inhibits biofouling with the help of dopamine. Various concentrations of coating were applied on the surface of the membrane. Surface of the modified membranes and anti-bacterial effect were analyzed. Modified membranes showed excellent inhibition of bacterial growth.